AKTIVITAS METAKOGNITIF MAHASISWA CALON GURU DALAM PEMECAHAN MASALAH - Murtafiah Murtafiah; Fauziah Hakim; Ana Muliana (PEDAMATH: Journal on Pedagogical Mathematics, 2019)
Metacognition is an important role in supporting students' success in mathematical problems solving. This study aims to describe the metacognitive activities of prospective teacher students in mathematical problems solving. The subjects of this study were as many as two people drawn from highly capable students with the consideration that the subjects were able to communicate / express their thoughts well. Data were collected using mathematical problem solving tests and interviews. Based on the results of data analysis, it was concluded that in each stage of solving mathematical problems consisting of 4 stages namely understanding the problem, planning the solution, carrying out the plan of completion, and checking again, the subject performs metacognitive activities namely planning activities (planning) thinking processes, monitoring thinking process, and evaluating the process and results of thinking.